Grammatical Cohesion Found in “Venom: Let There Be Carnage” Moviescript - Zani Hernawati; Ervina C.M. Simatupang (Budapest International Research and Critics University, 2022)
This research aims to analyzed the types of grammatical cohesion and analyzed the function of grammatical cohesion of speaker's utterance in Venom: